Exceptional state contemporary U.S. culture and the new imperialism - Dawson, Ashley 1965-; Schueller, Malini Johar 1957- (New Americanists, 2007)
Introduction : rethinking imperialism today / Ashley Dawson and Malini Johar Schueller -- Culture, US imperialism, and globalization / John Carlos Rowe -- Between the homeland and Abu Ghraib : dwelling in Bush's biopolitical settlement / Donald E. Pease -- Planet America : the revolution in military affairs as fantasy and fetish / Christian Parenti -- Hegemony and rights : on the liberal justification for empire / Omar Dahbour -- Updating the gendered empire : where are the women of occupied Afghanistan and Iraq? / Cynthia Enloe -- Techno-dominance and torturegate : the making of US imperialism / Malini Johar Schueller -- Left behind and the politics of prophecy talk / Melani McAlister -- Putting an old Africa on our map : British imperial legacies and contemporary US culture / Harilaos Stecopoulos -- New modes of anti-imperialism / Ashley Dawson -- Coda : information mastery and the culture of annihilation / Ashley Dawson and Malini Johar Schueller